Sidewalking : coming to terms with Los Angeles - Ulin, David L. (University of California Press, 2015)
"Sidewalking is an impressionistic take on Los Angeles in its current moment, which is a flashpoint of great transition, as the city verticalizes and densifies. It is also a meditation on the history, natural and human, of a place that often is derided as having no sense of its own past. What does it mean to live in, and think about Los Angeles at the level of its streets? Growing out of a series of walks, Sidewalking peels back the myths, the layers, to look at the city as it really is"--Provided by publisher